Review of the use of transition-metal-oxide and conducting polymer-based fibres for high-performance supercapacitors - Mohd Abdah, Muhammad Amirul Aizat; Azman, Nur Hawa Nabilah; Kulandaivalu, Shalini; Sulaiman, Yusran (Elsevier Ltd, 2020)
There is a growing interest in the application of supercapacitors in energy storage systems due to their high specific power, fast charge/discharge rates and long cycle stability. Researchers have focused recently on developing nanomaterials to enhance their capacitive performance of supercapacitors. Particularly, the utilisation of fibres as templates has led to theoretical and practical advantages owing to their enlarged specific surface area, which allows fast electrolyte-ion diffusion. In addition, the inclusion of redox-active components, such as transition metal oxides (TMOs) and conducting polymers (CPs), into the fibres is believed to play an important role in improving the electrochemical behaviour of the fibre-based materials. Nevertheless, supercapacitors containing TMO- and CP-based fibres commonly suffer from inferior ion-transport kinetics and poor electronic conductivity, which can affect the rate capability and cycling stability of the electrodes. Therefore, the development of TMO/CP-based fibres has gained widespread attention because they synergistically combine the advantages of both materials, enabling revolutionary applications in the electrochemical field. This review describes and highlights recent progress in the development of TMO-, CP- and TMO/CP-based fibres regarding their design approach, configurations and electrochemical properties for supercapacitor applications, at the same time providing new opportunities for future energy storage technologies.